2016
DOI: 10.1074/jbc.m115.669952
|View full text |Cite|
|
Sign up to set email alerts
|

myo-Inositol Oxygenase Overexpression Accentuates Generation of Reactive Oxygen Species and Exacerbates Cellular Injury following High Glucose Ambience

Abstract: increased ROS generation, depleted reduced glutathione, reduced GSH/GSSG ratio, and enhanced adaptive changes in the profile of the antioxidant defense system. These changes were also accompanied by mitochondrial dysfunctions, DNA damage and induction of apoptosis, accentuated activity of profibrogenic cytokine, and expression of fibronectin, the latter two being the major hallmarks of DN. These perturbations were largely blocked by various ROS inhibitors (Mito Q, diphenyleneiodonium chloride, and N-acetylcyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 66 publications
0
40
0
Order By: Relevance
“…[2] The pathogenesis of DKD is not clear, but mitochondrial abnormalities largely contribute to its development. [[3], [5]]. …”
Section: Introductionmentioning
confidence: 99%
“…[2] The pathogenesis of DKD is not clear, but mitochondrial abnormalities largely contribute to its development. [[3], [5]]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, we confirmed that Glucuronate-Xylulose (G-X) pathway was involved in the metabolism of MI in the proximal tubules of the kidney and MIOX served as the crucial enzyme [16]. Two different steps of the G-X pathway consume a large amount of NAD + .…”
Section: Discussionmentioning
confidence: 99%
“…We determined that MIOX expression is confined to renal proximal tubular cells and found that it is upregulated in the kidney of diabetic mouse. Current researches have shown that MIOX not only regulates MI metabolism but also participates in the pathogenesis of DN tubular injury through non-MI metabolic pathways, such as by stimulating the release of TGF β [15], disrupting the redox status [16] and regulating mitochondrial dynamics [17]. Interestingly, Gaut et al found that an increase in serum MIOX preceded the elevation of serum creatinine in patients with acute kidney injury (AKI), which was closely associated with the degree of tubular damage [18], indicating that serum MIOX can be used as an AKI biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors that are involved in generating oxidative stress during diabetes. There is strong evidence that hyperglycemia results in the activation of PKC in diabetic glomeruli and, as a consequence, mesangial expansion, glomerular basement membrane thickening, endothelial cell dysfunction leading to diabetic renal disease, inflammation, apoptosis [48][49][50]. Diabetic renal disease, on the other hand, intensifies the formation and activation of ROS, worsening renal disease [51].…”
Section: Impact Of Genetic Polymorphism On Gsts For Patients With Micmentioning
confidence: 99%